The Myth of Post-Reform Income Stagnation in Brazil - de Carvalho Filho, Irineu; Chamon, Marcos (Washington, D.C. : International Monetary Fund, 2006)
This paper uses Engel curves to estimate real income growth in Brazil. The estimated per capita household real income growth in metropolitan areas during 1987-2002 is about 4 1\2 percent per year, well above the "headline" growth of 1 1\2 percent obtained by deflating nominal incomes by the CPI. This suggests a substantial CPI bias during that period, likely owing to one-off effects of trade liberalization and inflation stabilization. The estimated unmeasured gains are higher for poorer households, implying a marked reduction in "real" inequality. This finding challenges the conventional wisdom that post-reform real income growth in Brazil was low.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet